Exploration of Thermal Performance of The Kulteka (Kuliner Tepi Kayan) Using the Effective Temperature Method - Arifiyanto, Hanik; Bonifacius, Nurhamdoko; Winansih, Erna (Proceedings of International Conference of Graduate School on Sustainability, 2025)
Bulungan Regency has one of the rivers, which serves as the core river, providing a source of economic, social, and cultural activities, namely the Kayan River. In the Kayan River, there is a trestle building 500 meters long and 15 meters wide. In 2006, the local government constructed a fish auction facility, known as TPI. During its development, the Fish Auction Place facility underwent a change in function to become the Culinary area, named Kulteka (Kuliner Tepi Kayan). This new function, which was not previously planned, drew the interest of many visitors, including both local residents and tourists from outside the region. Thermal comfort in the riverside culinary area is a major concern in creating a comfortable and attractive public space for visitors. There is a contradiction between the microclimate and thermal comfort in the Kulteka. So that the thermal comfort in this area is interesting to study. This study aims to analyze thermal comfort in the Kayan Riverside Culinary Area using a qualitative approach, with a focus on relative temperature. Microclimate data was collected through Onebuilding.org secondary data, then analyzed using relative temperature to identify the level of thermal comfort felt by local people and tourists from outside the region. This method allows a deeper understanding of the relationship between microclimate parameters and thermal comfort in open spaces. The study is expected to provide insight into the planning of riverside culinary areas that consider thermal factors to enhance resident comfort and support the development of an environment more conducive to the local microclimate.